PENGARUH KEPERCAYAAN, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DAN DAMPAKNYA TERHADAP PERPANJANGAN KONTRAK POLIS ASURANSI TANGGUNG GUGAT PROFESI DOKTER PADA PT. ASURANSI UMUM XYZ - Pratomo, Omie Gripio; Sutikno (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Currently, the population growth rate in Indonesia exceeds the increase in the number of existing health workers. It has potential problem for malpractice situation to arise due to fatigue or boredom in handling a unproportionate number of patients. This problem has become a business opportunity for PT. Asuransi Umum XYZ that since 20 years ago has been selling medical professional insurance protection policies to protect against malpractice suits. There was a decline in premium production and policy portfolios in 2019, so research is needed on the factors that influence customer loyalty over the last 5 years. This research aims to analyze the influence of factors on customer satisfaction and their impact on the contract extension of the Doctor's Professional Liability Insurance product policy at PT. Asuransi Umum XYZ. The factors currently being tested are Trust, Price or Premium Rate, Service Quality. The sample used was 210 customers of PT Asuransi Umum XYZ as respondents (Policy Holder Doctors). Research data was obtained from the results of filling out a questionnaire and analyzed using SEM analysis techniques. The sample collection technique in this research is non-probability purposive sampling. The type of research used is a descriptive analysis method with a quantitative approach. The results of this research show that : (1) trust has a positive and significant effect on customer satisfaction with p-value=0.013; (2) price has a positive and significant effect on customer satisfaction with p-value=0.004; (3) service quality has a positive and significant effect on customer satisfaction with p-value=0.002; (4) trust does not have an effect on loyalty because of p-value=0.175; (5) price has a positive and significant effect on loyalty with p-value=0.000; (6) service quality has a positive and significant effect on loyalty with p-value = 0.000; (7) satisfaction has a positive and significant effect on loyalty with p-value = 0.009. In the end, this research provides alternative input for companies to increase product sales results and encourages further researchers to analyze other marketing attributes.